2017
DOI: 10.5965/223811711632017269
|View full text |Cite
|
Sign up to set email alerts
|

Trocas gasosas de plantas de Handroanthus impetiginosus (Mart. ex DC) Mattos submetidas ao déficit hídrico e posterior reidratação

Abstract: Trocas gasosas de plantas de Handroanthus impetiginosus (Mart. ex DC) Mattos submetidas aodéficit hídrico e posterior reidratação PALAVRAS-CHAVE: eficiência no uso da água, fotossíntese, transpiração ABSTRACTKnowledge of aspects related to the ecophysiology of plant species present in Caatinga is scarce, needing studies that allow the understanding of the adaptations made by plants to be able to survive under conditions of low water availability. Accordingly, this study was developed with the purpose of analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
1
0
5
Order By: Relevance
“…However, some species adapted to arid and semiarid climate regions can reach this value without tissue death, which may be the case of M. tenuiflora plants in this research, since after the resumption of the supply of adequately restored their water status. These results agree with those found in the literature, in Handroanthus impetiginosus (Pessoa et al 2017), Myracrodruon urundeuva (Costa et al, 2015), Hevea brasiliensis (Chen et al, 2010), and Quercus pubecens (Gallé et al ., 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, some species adapted to arid and semiarid climate regions can reach this value without tissue death, which may be the case of M. tenuiflora plants in this research, since after the resumption of the supply of adequately restored their water status. These results agree with those found in the literature, in Handroanthus impetiginosus (Pessoa et al 2017), Myracrodruon urundeuva (Costa et al, 2015), Hevea brasiliensis (Chen et al, 2010), and Quercus pubecens (Gallé et al ., 2007).…”
Section: Discussionsupporting
confidence: 93%
“…The speed of response to the reduction in water availability varies by species, and the degree of this response directly affects the maintenance of plant tissue water balance. In H. impetiginosus seedlings, a 15% reduction in RWC was observed on the second day after the water supply was suspended (Pessoa et al 2017). These researchers also reported that at 10 days after irrigation suspension, RWC in irrigated and under water deficit plants were 83% and 26%, respectively, resulting in a 69% reduction.…”
Section: Discussionmentioning
confidence: 84%
“…O valor de TRA das plantas sob déficit hídrico (32%), no último dia de estresse hídrico, foi considerado baixo e crítico, de acordo com o valor estabelecido por Pardo (2010), considerando crítico TRA de 50%. Porém, foi superior ao obtido por Pessoa et al, (2017), em plantas de ipê roxo (Handroanthus impetiginosus (Mart. ex DC.)…”
Section: Resultsunclassified
“…O TRA como um dos aspectos determinantes da atividade metabólica e sobrevivência foliar, tem sido amplamente utilizado como um importante e eficaz indicador da tolerância das plantas à baixa disponibilidade de água no meio ambiente (PESSOA et al, 2017). No entanto, a resposta das plantas à redução na disponibilidade de água dependerá da espécie e do grau de estresse imposto.…”
Section: Resultsunclassified
See 1 more Smart Citation